(untitled) (Palíndromo, 2022)
This article seeks to understand the family legacy, real and imagery, in my artistic investigation process called "Self-portrait" an installation presented at the collective exhibition “Tramações”, in 2018, at the Capibaribe Gallery of the Arts and Communication Center of the Federal University of Pernambuco. I use my family history through objects captured and created in memories such as letters, written and transcribed memories that make up my imagination. In this scenario of memories, I also recreate and forge stories that are joining my story based on bonds between me and my family, especially the women who preceded me. Through the A/r/tographic narrative that allows me to address the congruence between my experiences as an artist, teacher and researcher, I ask the following question: how the rescue of female narratives, within the family, contributed to the process of creating the “Self-portrait”and what questions reverberated? Based on this, I take as a theoretical basis for this investigation the Studies of Gender and Sexualities, Collective Memory and the concept of Archivist Artist.